The Cambridge companion to women and Islam - Bano, Masooda (Cambridge companions to religion., 2025)
"This Companion provides a comprehensive overview of a timely topic that encompasses the fields of Islamic feminist scholarship, anthropology, history, and sociology. It considers the agency that Muslim women exhibit in relation to their faith as reflected in women's piety movements. Moreover, the volume documents how Muslim women shape socio-political life"--Provided by publisher.